2006
DOI: 10.1124/jpet.106.113035
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone Inhibits Epidermal Growth Factor-Stimulated Gastric Epithelial Cell Proliferation

Abstract: Epidermal growth factor (EGF) is essential to heal gastric ulcers, whereas glucocorticoid delays rat gastric ulcer healing. We found that dexamethasone inhibited EGF-stimulated rat gastric epithelial cell (RGM-1) proliferation by cell count and DNA synthesis analysis of flow cytometry and attempted to elucidate the possible mechanistic pathway via Western blot analysis. EGF (10 ng/ml) treatment for 24 h significantly increased RGM-1 cell proliferation, and dexamethasone (10 Ϫ8and 10 Ϫ6 M) markedly suppressed E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
19
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 37 publications
0
19
0
3
Order By: Relevance
“…Together with cyclin D and CDKs, p21 waf1 and p27 kip1 (hereafter referred to as p21 and p27) constitute targets of GR (5,45,50). Conversely, the activity of this receptor is also influenced by the phosphorylation promoted by cell cycle proteins (25,53).Throughout development, the administration of glucocorticoids exerts early inhibitory effects on gastric epithelial cell proliferation either in vivo or in vitro (20,21,35), besides inducing apoptosis (21). …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Together with cyclin D and CDKs, p21 waf1 and p27 kip1 (hereafter referred to as p21 and p27) constitute targets of GR (5,45,50). Conversely, the activity of this receptor is also influenced by the phosphorylation promoted by cell cycle proteins (25,53).Throughout development, the administration of glucocorticoids exerts early inhibitory effects on gastric epithelial cell proliferation either in vivo or in vitro (20,21,35), besides inducing apoptosis (21). …”
mentioning
confidence: 99%
“…In the absence of glucocorticoids, GR is found in cytoplasm as part of a large multiprotein complex, which contains heat shock proteins (HSPs), specifically HSP 70 and HSP 90 that allow the proper folding of the receptor and control entrance to the nucleus (23). After glucocorticoids bind GR, a conformational change releases the receptor from the complex, and it translocates into the nucleus to bind glucocorticoid-responsive elements at regulatory regions of target genes, to which repression is the most common response (23).GR arrests cell cycle through induction of antimitogenic factors and inhibition of proliferative molecules (35,45,50). Progression through cell cycle is accomplished by the formation of complexes between cyclins and cyclin-dependent kinases (CDKs), which are regulated by CDK-inhibitory proteins.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[58]. Luo et al [55,56] found that EGF activates extracellular signal-regulated kinase-1/2, then increases COX-2 expression and prostaglandin E 2 synthesis, increasing cyclin D1 expression, which promotes RGM-1 cell proliferation. This was reversed with dexamethasone, which may interfere with EGF binding to its receptor or EGF activation of extracellular signalregulated kinase-1/2, thereby delaying ulcer repair.…”
Section: Glucocorticoidsmentioning
confidence: 98%
“…Previously, it was discovered that dexamethasone delayed rat gastric ulcer healing by inhibiting epithelial cell proliferation and angiogenesis at the ulcer margin and base, via COX-2 and prostaglandin E 2 inhibition [55]. A recent study demonstrated that dexamethasone strongly inhibits epidermal growth factor (EGF)-stimulated gastric epithelial cell proliferation [56]. EGF promotes gastric ulcer healing by upregulating gastric epithelial COX-2 expression [57] and by activating the Ras/Raf/mitogen-activated Methionine, an essential amino acid, is obtained by dietary intake and transported to the liver mainly by the System L. Methionine adenosyltransferase (MAT) catalyzes the ATP-dependent conversion of methionine to S-adenosylmethionine, which is converted to S-adenosylhomocysteine by the glycine N-methyltransferase (GNMT) and then hydrolyzed to homocysteine.…”
Section: Glucocorticoidsmentioning
confidence: 98%